Dual arm co-manipulation architecture with enhanced human–robot communication for large part manipulation - Ibarguren, Aitor; Eimontaite, Iveta; Outón, José Luis; Fletcher, Sarah (MDPI, 2020)
The emergence of collaborative robotics has had a great impact on the development of robotic solutions for cooperative tasks nowadays carried out by humans, especially in industrial environments where robots can act as assistants to operators. Even so, the coordinated manipulation of large parts between robots and humans gives rise to many technical challenges, ranging from the coordination of both robotic arms to the human–robot information exchange. This paper presents a novel architecture for the execution of trajectory driven collaborative tasks, combining impedance control and trajectory coordination in the control loop, as well as adding mechanisms to provide effective robot-to-human feedback for a successful and satisfactory task completion. The obtained results demonstrate the validity of the proposed architecture as well as its suitability for the implementation of collaborative robotic systems.
Keywords: human–robot interaction; co-manipulation; human–robot interface; assistant robots